Implementasi Pembelajaran Matematika Berdiferensiasi di Sekolah Dasar pada Kurikulum Merdeka - Caesaria, Nomalika Zindagi; Saputra, Yohan Dwi; Siswanto, Deny Hadi (MURABBI, 2024)
Differentiated instruction is an approach that places students at the center of learning, considering their needs, interests, and individual abilities to create inclusive and meaningful learning experiences. This study aims to analyze the implementation of differentiated mathematics instruction by teachers at Muhammadiyah Canden Elementary School using a qualitative descriptive approach. Data were collected from the analysis of previous research journals, validated through source and technique triangulation. The findings indicate that the Merdeka Curriculum provides teachers with flexibility to develop adaptive thematic learning. The implementation of differentiated instruction involves task variations, student grouping, and the use of tailored teaching modules. This study concludes that differentiated instruction has significant potential to enhance educational quality within the Merdeka Curriculum framework. Recommendations are provided to strengthen collaboration between teachers, schools, and parents, as well as to ensure adequate policy support for the optimal implementation of differentiated instruction